Development of catsup from the optimum level of banana flour - Co, Louis G.
This is a study of the feasibility of substituting banana flour for fresh banana in catsup. Banana flour at 1.74% and 2.73% levels based on the weight of fresh banana was incorporated into a standard recipe for catsup formulated by Lafuente in 1972. Analysis was made on the soluble solids (SS), titratable acidity (TA), pH and consistency of the finished products. A descriptive scorecard analyzing color, texture, flavor, consistency and general acceptability of the products was presented to a panel of ten judges. Results of the sensory evaluation analyzed by ANOVA and the Duncan's Multiple Range Test show that there are statistical differences between the two samples with respect to flavor, color, texture, consistency and general acceptability at the 5% level of significance. Based on over-all sensory and objective evaluations, the sample containing 1.74% of banana flour based on the fresh banana was judged as the more acceptable sample.